Hypnotic Learning Characteristics On Sisya Brahmakunta Community In Denpasar - I Putu Suweka Oka Sugiharta; I Ketut Sudarsana (Institut Hindu Dharma Negeri Denpasar, 2017)
Hypnotic learning at Brahmakunta Community in Denpasar City is complementary the scienceof education by paying attention to aspects of interpersonal needs of learners, integral evolution on the students, as well as various aspects of his personality. Hypnotic contribution in education can align the senses of the learner, harmonize his mind, and make manusamadhawa (man who has the divine character).Through the approach of psychology of religious education supported by the of FIRO theory (the theory of the basic relationship between by William Schutz, evolutionary psychology theory by Robert C. Bolles, and the theory of Field Psychology by Kurt Lewin. Data obtained by in-depth interviews, study documentation then the data is interpreted by looking for deep meaning. The characteristics of hypnotic learning in the Brahmakunta community indicate the aspect of the basic needs of the learners so that the learning process is not disturbed.The characteristics of hypnotic learning in the community of Brahmakunta include: (a) the attached characteristic shown to meet the needs of the assimilation, (b) Control Characteristics that aim to meet the needs of ideally positioning themselves, (c) The characteristics of Affection aimed at meeting the needs of affection, and (d) The compatibility characteristics that indicate that learning is done to improve interpersonal relationships.